Réponses

2014-03-03T20:39:38+01:00
A) 7x = 21
x = 21/7
x = 3

b) -3x = 12
x = -12/3
x = -4

c) 5x - 25 = 0
5x = 0 + 25
5x = 25
x = 25/5
x = 5

d) 4x - 3 = 5
4x = 5 + 3
4x = 8
4x/4 = 8/4
x = 8/4
x = 4

e) 4x + 2 = x + 11
2 + 4x = x + 11
2 + 4x + -1x = 11 + x + -1x
4x + -1x = 3x
2 + 3x = 11 + x + -1x
x + -1x = 0
2 + 3x = 11 + 0
2 + 3x = 11
2 + -2 + 3x = 11 + -2
2 + -2 = 0
0 + 3x = 11 + -2
3x = 11 + -2
11 + -2 = 9
3x = 9
x = 3


f) 3x - 7 = - 2x - 9
-7 + 3x = -2x + -9
-7 + 3x = -9 + -2x
-7 + 3x = -9 + -2x
-7 + 3x + 2x = -9 + -2x + 2x
 3x + 2x = 5x -7 + 5x = -9 + -2x + 2x
-2x + 2x = 0
-7 + 5x = -9 + 0
-7 + 5x = -9 
-7 + 7 + 5x = -9 + 7
-7 + 7 = 0
0 + 5x = -9 + 7
5x = -9 + 7
-9 + 7 = -2
5x = -2
x = -0,4



merci , merci , mercii ❤️
Je t'ai tout détaillé pour que tu comprennes :)
merci beaucoup :3